Municipal solid waste incineration ash as cassion infill - Teo, Darryl Jie Shun (Nanyang Technological University, 2023)
This study investigates the feasibility of using mixed materials, consisting of incinerator bottom ash, incinerator fly ash and non-incinerable waste, as infill for caisson structures. Durability of concrete would be the focus of this study through characterising the interactions between mixed material and seawater. Samples were collected from Pulau Semakau landfill, at different depths, to obtain a representative sample of the entire landfill. Leaching using deionised water was conducted on all samples to determine their leaching profiles. Twenty samples of mixed materials were further selected based on the most critical leachate obtained during leaching. Modified batch and cumulative leaching tests were then conducted using seawater to investigate the types of heavy metals and ions being leached out, as well as to determine the buffer capacity of the mixed materials to undergo further ionic leaching. Results indicate that the levels of chloride and sulphates were higher than those found in seawater, which are the main durability concerns for concrete. Heavy metal ions were found to have limited influence on concrete durability. These findings suggest that a thicker concrete cover may be needed to retain similar durability, but that no modification to concrete mix design is necessitated when using mixed material as concrete caisson infill. This study provides important insights for caisson design and the use of mixed materials in marine applications, including recommendations for further research on concrete durability and the long-term performance of mixed materials.